The Existence of Tutoring Institutions: How Much does it Contribute to Student Achievement in Palu City? - Nanda Diva; Exsa Putra; Suwarni; Amalia Novarita (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to analyse the effect of the contribution of tutoring institutions on student learning outcomes. The study used a quantitative approach with a correlational method. The research subjects consisted of 75 students in grades X and XI of high schools in Palu City who were selected using purposive sampling technique between two tutoring institutions, namely Ganesha Operation and Brain Academy Teachers’ Palu. The data analysis technique used was simple linear regression with the help of SPSS. The results showed an increase in students' scores after attending tutoring. At Ganesha Operation, the average student score increased from 79.64 to 91.80, while at Brain Academy Teachers’ the average student score increased from 83.40 to 90.64. However, the regression test results show that the contribution of tutoring institutions does not significantly affect student learning outcomes. The regression coefficient value at Ganesha Operation is 0.032 with a significance of 0.036 (>0.05), while at Brain Academy Teachers’ it is 0.889 with a significance of 0.480 (>0.05). Thus, it can be concluded that the existence of tutoring institutions still has a low contribution to improving student learning outcomes, especially in Geography subjects.